We begin at the end [compact disc, unabridged] - Whitaker, Chris (Macmillan Audio, 2021)
A guilt-ridden police chief and a tough-as-nails woman who was forced to support her family as a girl work together to protect loved ones when the latter's father is released after thirty years in prison.